Narrowband performance of active control on flow-induced vibrations inside hard disk drives - Min, Hequn (2013)
This paper presents an experimental study of digital narrowband active control on the flow-induced vibrations (FIV) on the head gimbals assembly (HGA) in a working hard disk drive (HDD). Firstly, the modal testing on the HDD was carried out, in which the disk modes were analyzed with a 1-D laser Doppler vibrometer (LDV) and the HGA vibration modes with a 3-D LDV. Secondly, a digital feedback control closeloop was implemented in experiments to suppress the FIV spectrum peaks on the HGA. In this close-loop, the HGA vibrations detected by the LDV were used as feedback error signals, then the signals was passed through a digital controller to generate feedback signals to drive a piezoelectric disk to actuate feedback acoustic pressure around the HGA. Active control experiments were conducted in narrow bands on five principal peaks in the HGA off-plate vibration spectrum, around 1256Hz, 1428Hz, 2141Hz, 2519Hz and 3469Hz, respectively. It is shown that distinct suppression of at least 10 dB can be achieved on all these HGA vibration peaks.